Analysis of the Procedural Controller Function on Workload at the Area Control Centre (ACC) JATSC - Rosa Mustika; Rahmawati Sukra; Imam Sonhaji (CV. AFDIFAL MAJU BERKAH, 2026)
This study analyzes the function of procedural controllers and its influence on workload at the Area Control Centre (ACC) within the Jakarta Air Traffic Service Centre (JATSC). Unlike radar controllers who operate with real-time visual aids, procedural controllers rely on communication, coordination, and pilot reports, resulting in a higher mental and cognitive workload. The research aims to identify how procedural control functions contribute to workload levels and how these functions can be optimized to maintain operational safety and efficiency. The study adopts a quantitative method with a descriptive-correlation approach. Data were collected through observations, semi-structured interviews, and closed-ended questionnaires using a five-point Likert scale. Respondents consisted of active Air Traffic Controllers (ATCs) at ACC JATSC, selected using purposive sampling with at least one year of work experience. Data analysis was performed using multiple linear regression to evaluate both simultaneous and partial effects of procedural control functions on workload. The findings show that high adherence to standard operating procedures (SOP), consistent application of procedures, and effective communication significantly reduce perceived workload. However, procedural controllers continue to face moderate-to-high levels of mental and physical workload due to sustained cognitive demands, communication intensity, and time pressure. The study concludes that optimizing procedural control functions serves as a protective mechanism against excessive workload, supporting safety, efficiency, and the well-being of ATC personnel at JATSC.